Public attitudes towards research participation during an infectious disease pandemic: a qualitative study across four European countries. (November 2016) - Gobat, Nina; Gal, Micaela; Butler, Christopher C; Francis, Nicholas A; Anthierens, Sibyl; Bastiaens, Hilde; Godycki-ćwirko, Maciek; Kowalczyk, Anna; Pons-Vigués, Mariona; Pujol-Ribera, Enriqueta; Berenguera, Anna; Stanton, Helen; et al.
Abstract: Background: Pandemics of infectious disease are recurrent events that impact global health and security. International, collaborative planning for future pandemics is a priority for public health officials, the research community, and the general public. However, little is known about the public's attitudes to participating in pandemic research and about their views on associated ethical dilemmas. We aimed to determine public perceptions about involvement in clinical research conducted in primary and critical care during a pandemic. Methods: We conducted ten, 2 hour focus groups (6–10 participants each) and 16 one-to-one follow-up interviews involving 80 members of the public in Belgium, Poland, Spain, and the UK between Sept 1 and Dec 31, 2015. Recruitment was through local advertisement. Data were collected by local researchers who followed a scenario-based topic guide, transcribed verbatim and translated into English. We used framework analysis to identify the range and diversity of participants' perspectives. Findings: Public understandings of pandemics were shaped by personal factors (illness during the H1N1 pandemic, experience of life-threatening illness) and social factors (historical references, media, public health information). Motivations to participate in pandemic research were influenced by altruism, therapeutic misconception, trust, and perception of risk. Use of routinely collected data and clinical samples without explicit prior consent was supported in principle, but was less acceptable when a profit motive was perceived. Participants recognised and appreciated the protections provided by ethically robust research procedures. However, they described having become desensitised to the importance and meaning of consent processes because of the frequency with which they authorise terms and conditions in everyday life. Participants proposed different models that might apply in a pandemic context (eg, advanced consent, verbal consent). Interpretation: Public engagement in clinical research on pandemic planning is possible, useful, but as yet underdeveloped in Europe. Effective pandemic preparation for clinical research requires active public engagement to mitigate therapeutic misconception and engender trust. This bottom-up approach to ascertaining public views on pandemic research participation has identified support for minimising disproportionate research protection procedures for publicly funded, low risk studies. Funding: European Union Seventh Framework Programme under the project Platform foR European Preparedness Against (Re-)emerging Epidemics (PREPARE) (grant agreement 602525).